Evaluation of Learning Media Creation Based on Results of Computational Chemistry Calculations Visualised - Nilmarito, Suriati; Lestari, Siska; Mantondang, Silvia Elatastari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The objective of this study is to determine the outcomes of the requirements analysis and learning materials for electrolyte and non-electrolyte solution materials. Additionally, learning materials will be developed utilising computational chemical calculations and visualisation of the results to create learning media based on the National Education Standards Agency (BSNP) requirements. This kind of study uses the ADDIE development model and is referred to as development research. There are five steps in the current ADDIE model: analysis, design, development, implementation, and evaluation. The entire student body of one of the senior high schools in Padangsidempuan City, North Sumatera, Indonesia, served as the study's population. The participants in this research were senior high school students from Padangsidempuan City, North Sumatera, Indonesia. The use of a purposive sampling technique yields grade X as the research sample. An inquiry form derived from the National Education Standards Agency was used as the research tool. Utilising a significance level of 5%, the data analysis was conducted using the SPSS 22 for Windows software. The investigation's findings demonstrate the need for educational materials to help pupils struggling with learning. Based on 95% validation findings, the learning materials for both electrolyte and non-electrolyte solutions visualise the outcomes of computational chemical calculations.